Teachers' Silent Scream: Quiet Quitting - Memis, Tugba Konal; Tabancali, Erkan (TURKISH EDUCATIONAL ADMIN RESEARCH & DEVELOPMENT ASSOC, 2024)
The aim of the study is first to discover if quiet quitting (QQ) act exists among teachers at schools, and then, if there are teachers who are a part of this movement, to disclose the indications of QQ act and the reasons that push them to quiet quit. The study was designed in accordance with the qualitative phenomenology pattern and carried out with 13 teachers selected by the snowball sampling method, which is one of the purposive sampling methods. Semi-structured faceto-face interviews were conducted to collect data and the data was analyzed by content analysis technique. In the light of the analysis, indications of QQ among teachers and reasons for QQ among teachers themes emerged. The result of the study reveals that teachers are part of the QQ act. Teachers' ending their psychological contract, organizational commitment and belonging are internal indications, while holding back on duties that are outside the job description, not taking on new duties, and not taking responsibility for duties requiring them to spend overtime or outside working hours are external symptoms. As for the reasons, teachers quiet quit because the meaning they attach to their profession is deteriorated and their efforts are rendered worthless because of the financial challenges they experience. Also, due to the precarization they experience stemming from the paid teaching practice and the loss of prestige in the society, teachers quiet quit. Pandemic is among the other reasons that lead teachers to quiet quit. Furthermore, work-life imbalance pushes teachers to question their profession and they regard QQ as a way out of that imbalance. Lastly, low motivation and commitment are regarded as the reasons for QQ among teachers. Accordingly, it is recommended to make the precarization process of the teaching profession visible, to abolish the practice of paid teaching, to regulate teacher salaries below the poverty line, to revise excessive workload causing work-life imbalance, to limit the expectation of being available outside of work hours, and to eliminate the elements that undermine teachers' organizational motivation and commitment.
Keywords: Quiet quitting; teachers' quiet quitting; psychological contract breach; counterproductive work behavior; organizational citizenship behavior; indications of quiet quitting; reasons for quiet quitting; PSYCHOLOGICAL CONTRACT; Education & Educational Research